2021
DOI: 10.1038/s41467-021-22163-7
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation controls the binding of hexokinase 2 to mitochondria and protects against prostate cancer tumorigenesis

Abstract: Human hexokinase 2 is an essential regulator of glycolysis that couples metabolic and proliferative activities in cancer cells. The binding of hexokinase 2 to the outer membrane of mitochondria is critical for its oncogenic activity. However, the regulation of hexokinase 2 binding to mitochondria remains unclear. Here, we report that SUMOylation regulates the binding of hexokinase 2 to mitochondria. We find that hexokinase 2 can be SUMOylated at K315 and K492. SUMO-specific protease SENP1 mediates the de-SUMOy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 42 publications
0
63
0
Order By: Relevance
“…Both Thr-473 and Lys-63 are absent in the other HK isozymes, suggesting that HK2 binding to mitochondria underpins unique and distinct biochemical functions. In addition, it was recently demonstrated that HK2 can be SUMOylated at Lys-315 and Lys-492 residues and that de-SUMOylated HK2 preferably binds to mitochondria [ 81 ].…”
Section: Hk2 On Mitochondria Of Neoplastic Cells: Maintaining the Bad Guy In Perfect Shapementioning
confidence: 99%
“…Both Thr-473 and Lys-63 are absent in the other HK isozymes, suggesting that HK2 binding to mitochondria underpins unique and distinct biochemical functions. In addition, it was recently demonstrated that HK2 can be SUMOylated at Lys-315 and Lys-492 residues and that de-SUMOylated HK2 preferably binds to mitochondria [ 81 ].…”
Section: Hk2 On Mitochondria Of Neoplastic Cells: Maintaining the Bad Guy In Perfect Shapementioning
confidence: 99%
“…PTEN is considered to serve as a barrier for SENP1-induced PCa tumorigenesis, and the inhibition of SENP1 may be a therapeutic option for treatment of aggressive PTEN-deficient PCa. SUMOylation controls the subcellular localization of hexokinase 2 (HK2), which is a regulator of glycolysis and has oncogenic potential when it binds to mitochondria [239]. SENP1-induced deSUMOylation stimulates HK2 binding with mitochondria to promote metabolic reprogramming, supporting proliferation of PCa cells and protecting them from chemotherapy-mediated apoptosis.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Dysregulation of SUMO pathway can also promote resistance towards several anti-cancer drugs, such as the proteasome inhibitor bortezomib in MM, anti-estrogens in breast cancer and different chemotherapeutics. Docetaxel resistance in PCa can be triggered via overexpression of the SENP1-HK2 axis or overexpression of PIAS1, further emphasizing heterogeneity of SUMO-dysregulation in cancer [239,303]. Hypoxia-induced SUMOylation of self-renewal and pluripotency regulator OCT4 decreases its level in embryonal carcinoma cells and promotes cisplatin and bleomycin resistance that can be counteracted with the induction of SENP1 overexpression [304].…”
Section: Potential Rational Combinationsmentioning
confidence: 99%
“…Increasing evidences have proven that the excessive activation of glycolysis mediates cell proliferation, resistance to chemotherapy, the immune response, and distant metastasis ( 15 , 37 – 39 ), so targeting aerobic glycolysis has become a promising treatment strategy ( 40 ). In the present study, the molecular functions of five glycolytic genes were investigated in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…This unique metabolic signature termed Warburg effect has been demonstrated to exist in various solid tumors, including PCa (12)(13)(14). Recently, an increasing number of studies have reported that abnormal expression of glycolysisrelated molecules have crucial roles in regulating chemotherapy resistance (15), immune response (16,17), neuroendocrine differentiation (18), and growth and metastasis of PCa (19,20), ultimately affecting its prognosis. Additionally, some researchers have successfully constructed prediction models derived from glycolysis-associated genes in liver cancer and colon cancer (4,21).…”
Section: Introductionmentioning
confidence: 99%